Pengaruh Model Pembelajaran Experiental Learning terhadap Hasil Belajar Siswa Geografi Kelas XII IPS di SMA N 1 Palupuh Kabupaten Agam - Fitri, Hilma; Nova, Sari (Al-DYAS, 2024)
This study aims to determine the effect of the application of the Experiential Learning learning model in improving student learning outcomes in geography subjects at SMA N 1 Palupuh, Agam Regency. This type of research is quantitative, with pseudo-experimental methods. The research design used was pretest-posttest Control Group Design. The research sample was class XII IPS 1 as an experimental class and class XII IPS 2 as a control class. The sampling technique uses purposive sampling with a sample of 40 people. Based on the results of this study, the results of the hypothesis test were obtained, namely the results of the t test where the value of Tcalculate (4.413) > Ttable (1.686). Thus, Ha is accepted and H0 is rejected. It can be concluded that there is an influence of the Experiential Learning learning model on student learning outcomes in class XII social studies geography subjects at SMA N 1 Palupuh, Agam Regency.